Pengaruh penebangan hutan terhadap kesejahteraan masyarakat di Asmat - Aditjondro, George J. (George Junus), 1946- (Yayasan Pengembangan Masyarakat Desa Irian Jaya, 1985)
Impact of deforestation on socioeconomic conditions of the Asmat people in the southwestern part of Irian Jaya Province.